Menilik Perkembangan Kesenian Orek-Orek pada tahun 1932 – 1980 sebagai kesenian daerah Kabupaten Ngawi dalam perspektif kesenian pendatang: Arts, Orek-Orek, Local, Ngawi, Netherlands. - SUNANDAR PRIYO SANTOSO (Historia Pedagogia, 2025)
Orek-Orek art is an art that underwent reconstruction during its development so that it was able to influence changes in the fate of forced laborers during the Dutch Colonial period. In this research, the author uses a historical method, which in the process of compiling a written work consists of four stages including (Heuristics, Source Criticism, Source Interpretation, and Historiography). There are at least 2 problem formulations that the author wants to study, namely 1. What is the history of the birth of Orek-Orek art? 2. How did Orek-Orek art develop during the colonial period until after independence. This research aims to provide a new reading source related to the local history of Ngawi Regency from an artistic perspective. The results of this research are that Orek-Orek art first appeared in 1932 in the Ambarawa area. At first this art was performed to symbolize the inauguration of the Bridge and Dam Project in Ambarawa during the Dutch Colonial Period. In its development, this art experienced changes in movement and motifs, which initially only consisted of various movements accompanied by gamelan music, then developed into an art resembling kethoprak, which contains story elements in the form of drama in the performance. As time went by, this art faded and disappeared due to people's interest turning to kethoprak art. The art of Orek-Orek began to emerge back in 1980, which was initiated based on the creativity of Mrs. SrI Widajati who created the Orek-Orek Dance as a typical art of Ngawi Regency. Orek-Orek art depicts the social values ​​and conditions of Ngawi Regency, on a basic basis.